Discursive Constructions of Child Rape in Pakistani Newspapers: A Study of Hussain Khan Wala Case - Muhammad Waqas Butt; Shaira Zaman; Raana Malik (Sustainable Business and Society in Emerging Economies, 2022)
Purpose: This study identifies the types and nature of media discourses of child rape that may be intended to maintain gender ideologies and power relations around normative sexual practices.